Fostering sustainable siswapreneurship: collaborative strategies from university, government, and private sector support / Aida Nur Mohd Kodri … [et al.] - Mohd Kodri, Aida Nur; Ahmad, Siti Nurul Akma; Mohd Nor, Khalijah; Wan Mohamad Saferdin, Wan Aisyah Amni; Abu Karim, Rizuwan; Zamri, Muhammad Hafizi; Muhamad Hanapiyah, Zulkefli (2023)
Malaysia is not an exception when it comes to employability challenges, which are becoming more serious by the year. The cooperation of universities, governments, and private enterprises is critical in supporting the national goal in the growth of entrepreneurship in Malaysia and ensuring the sustainability of entrepreneurial fields. The goal of this study was to identify the role of the triple helix model for siswapreneur development and sustainability. The qualitative research method was used in this study. The information was gathered through semi-structured interviews. The interview session included 14 siswapreneurs as a sample. The interview transcripts were coded and analyzed using a thematic analytics approach. The study's findings indicate that the involvement and support of universities, government agencies, and private corporations is critical if they are to be successful as entrepreneurs after graduation. The limitation of this study is that the respondents are only from Universiti Teknologi MARA (UiTM) Melaka Branch. This finding is expected to serve as a guide for policymakers, specifically the Ministry of Higher Education, in applying the triple helix model to boost siswapreneur development in higher education institutions. This study presents the important involvement of university, Government agencies and Private corporations in supporting the sustainable siswapreneur.